Feasibility of using calcined patinopecten yessoensis shells for fluoride removal and investigation of the fluoride removal mechanism - Choi, Moon Yeong; Lee, Jae In; Lee, Chang Gu; Park, Seong Jik (Desalination and Water Treatment, 2021)
This study assessed the applicability of seafood waste, Patinopecten yessoensis shells (PY), for fluoride removal. PY was modified by calcination to improve its fluoride removal capacity, and 800°C was the optimum calcination temperature its modification as a fluoride adsorbent. Fluoride adsorption by PY-800 was confirmed due to the formation of fluorite (CaF2) through X-ray diffraction analysis. The fluorine adsorption to PY-800 reached equilibrium within 2 h at an initial fluoride concentration of 50 mg/L, and a reaction time of 36 h was required to reach equilibrium at 200 mg/L. Both the pseudo-first-order and pseudo-second-order models described the kinetic adsorption data well. In isotherm studies, the fluoride adsorption of PY-800 was best suited to the Langmuir model. The enthalpy change of fluoride adsorption was 45.49 kJ/mol, ranging in the boundary between physical and chemical adsorption. Fluoride adsorption decreased from 113.13 to 86.01 mg/g as the pH increased from 3 to 11. Anions in the solution inhibited fluoride adsorption, and impacted other ions in the following order: chloride < sulfate < carbonate < phosphate. PY-800 has a higher adsorption capacity than other reported adsorbents, with a maximum of 159.62 mg/g. These results show that PY-800 recycled from food waste is highly efficient for fluoride removal.
Keywords: Adsorption mechanism; Fluoride removal; Patinopecten yessoensis shells; Scallop shell; Thermal treatment